Analisis Peran Bimbingan Orang Tua Dan Guru Terhadap Prestasi Belajar Peserta Didik Pada Mata Pelajaran Matematika di Kelas V MI NW Tenges-Enges - Ozi Satria; Wiranda Putra; Muhammad Kiradi; Lalu Wahyu Hidayat (Pendidikan Al-Gafari, 2024)
Education for human life is an absolute life that must be fulfilled throughout life. Without education, a group of people will find it difficult to live and develop in line with their ideals to progress. This study aims to: 1) determine the role of parental and teacher guidance on student learning achievement in mathematics, 2) determine the challenges of parents and teachers in guiding students, and 3) determine the increase in student learning achievement at MI NW Tenges-Enges. The type of research used is descriptive qualitative research. Data collection techniques used in this study are observation, interviews, and documentation. The results of this study conclude the role of parental and teacher guidance on student learning achievement in mathematics in class V MI NW Tenges-Enges, where the role of teacher guidance has been running well and the role of adult guidance is still not running well because there are parents who are still less able to divide their time between work and guiding children, do not understand the material and parents do not know what to do when they have to guide students in studying at home. The suggestions based on the research that has been done are: 1) for teachers, teachers must be patient in guiding students, especially in explaining the material, guiding students who are less focused during learning and students who rarely attend school. 2) students, should understand the study time and playtime during learning. 3) parents, must pay more attention to children in learning, especially parents must be able to divide their time to guide children in learning.